Human Resource Development Methods During the Covid-19 Pandemic and New Normal in Matahari Department Store Retail Business Companies Armada Town Square Magelang - Nathania Evanthe; Johnson Dongoran (Quantitative Economics and Management Studies, 2023)
The aim of this research is to identify methods for developing human resources, efficiency and effectiveness, as well as the benefits obtained by employees and companies after training is held during the Covid-19 pandemic and the New Normal. This type of research is qualitative research using primary data, the researcher conducted a short interview with the head of HRD Matahari Department Store Magelang and distributed questionnaires to 20 respondents who were employees of Matahari Department Store Magelang. Data were analyzed using the Miles and Huberman model analysis technique. The results in this research show the methods of developing human resources on-the-job training and off-the-job training, the efficiency and effectiveness of training, and the benefits of training for employees and companies